Associations of Dietary Patterns and Incident Type 2 Diabetes in a Community Population Cohort From Southwest China - Wang, Yanhuan; Xu, Lina; Wang, Na; Zhu, Ling; Zhao, Fouxi; Xu, Kelin; Liu, Tao; Fu, Chaowei (Frontiers in Public Health, 2022)
Background The prevalence of type 2 diabetes (T2D) is rising rapidly worldwide, but there are scant empirical data on the association between diet and diabetes in Southwest China. Methods In this prospective community-population cohort study from Guizhou Province, China since 2010, 7,023 eligible adults were included. Dietary information was obtained by face-to-face interviews with a semi-quantitative food frequency questionnaire, and dietary patterns were derived by factor analysis. The hazard ratios (HR) and 95% confidence intervals (95% CI) were estimated for the associations between various dietary patterns and incident T2D risk by cox proportional hazard model. Results Until 2020, a total of 749 new T2D cases were identified during the average follow-up of 7.05 years and the incidence was 14.75/1,000 person-years. Two main dietary patterns from the food frequency questionnaire were identified by factor analysis, i.e., vegetable-grain pattern and junk food pattern. In the multivariate analysis, 28 and 20% lower risks of T2D were observed at the low intake of junk food pattern (HR: 0.72, 95% CI: 0.61, 0.87) and the high intake of vegetable-grain pattern (HR: 0.80, 95% CI: 0.67, 0.95) after adjustment for potential confounding factors, compared with the medium intake of such patterns, respectively. Positive linear relationships were found between fasting plasma glucose (FPG) at follow-up and its change with junk food pattern, while there were inverse linear associations with vegetable-grain pattern. Conclusion Higher adherence to vegetable-grain patterns and lower adherence to junk food patterns significantly lowered T2D incidence among the population in Southwest China. Moving toward a healthier dietary model deserves more attention to develop interventions for the prevention of T2D.